2017
DOI: 10.21873/anticanres.11657
|View full text |Cite
|
Sign up to set email alerts
|

Diversified β-2-adrenergic Receptor Expression and Action in Melanoma Cells

Abstract: Melanoma cell susceptibility to AD varies depending on origin and progression stage. Metastatic cutaneous melanoma cells were found to be less responsive to AD than primary cutaneous and uveal melanoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…3-T 1 AM has also been described as an antagonist of muscarinic type 3 receptor (Laurino et al, 2016 ). Furthermore, beta-adrenergic receptors and muscarinic receptors are expressed in multiple melanoma cells including primary uveal melanoma (92.1, Mel202) (Janik et al, 2017 ). In addition, changes in K + channel activity have been implicated in modulating progression of melanoma (Oppitz et al, 2008 ; Luo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…3-T 1 AM has also been described as an antagonist of muscarinic type 3 receptor (Laurino et al, 2016 ). Furthermore, beta-adrenergic receptors and muscarinic receptors are expressed in multiple melanoma cells including primary uveal melanoma (92.1, Mel202) (Janik et al, 2017 ). In addition, changes in K + channel activity have been implicated in modulating progression of melanoma (Oppitz et al, 2008 ; Luo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and clinical data suggest a role of adrenaline and noradrenaline, neurotransmitters from the sympathetic NS, in the regulation of melanoma progression 24,27,65 . Thanks to the expression of the adrenergic receptors, human melanoma cells can respond to the catecholamines inside the TME.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some preclinical studies have demonstrated the role of autonomic NS neurotransmitters such as adrenaline, noradrenaline, aka catecholamines, and acetylcholine in cancer progression 22,23 . Indeed, β1, β2 and β3 catecholamine receptors, physiologically expressed in different tissues and organs, to regulate vital body functions have been also detected in the membrane human melanoma samples and melanoma cell lines 24,25,26 . Activation of β-receptors seem to support cell proliferation, while inducing migration and invasion phenotypes and an EMT-like process in melanoma cells in vitro 24,27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha (α)-adrenoceptors and beta (β)-adrenoceptors are expressed in both melanoma tissue samples and various melanoma cell lines [ 38 , 56 , 57 , 58 ]. However, adrenergic receptor expression and melanoma cell response to adrenergic stimulation are dependent on both the receptor and the cell type [ 59 ].…”
Section: Neurotransmitters and Melanomamentioning
confidence: 99%